Physical Activity Levels and Differences in the Prevalence of Diabetes Between the United States and Canada - Zhang, X. P. (2012)
Objective. To examine the American-Canadian difference in physical activity and its association with diabetes prevalence. Methods. We used cross-sectional data from nationally representative samples of adults (8688 persons aged 18 years) participating in the 2004 Joint Canada/U.S. Survey of Health. Using data on up to 22 activities in the past 3 months, we defined 3 physical activity groups (in metabolic equivalents-hours/day) as low (= 3.0). We employed logistic regression models in our analyses. Results. Self-reported diabetes prevalence was 7.6% in the U.S. and 5.4% in Canada. The prevalence of low physical activity was considerably higher in the U.S. (70.9%) than in Canada (52.3%), while levels of moderate and high physical activity were higher in Canada (24.6% and 23.1%, respectively) than in the U.S. (14.3% and 14.8%, respectively). Using nationality (Canada as reference) to predict diabetes status, the adjusted odds ratio was 1.48 (95%CI, 1.22-1.79), and became 1.38 (95%CI, 1.15-1.66) when additionally adjusting for physical activity level. We estimate that 20.8% of the U.S.-Canada difference in diabetes prevalence is associated with physical activity. Conclusions. The difference in the prevalence of diabetes between U.S. and Canadian adults may be partially explained by differences in physical activity between the two countries. Published by Elsevier Inc.